SUN-335 Abaloparatide Prevents Unloading-Induced Bone Loss in Adult Rats - Teguh, Dian A (J Endocr Soc, 2020)
Disuse osteoporosis (bone loss resulted from a reduction in mechanical loading) occurs in patients due to prolonged bed rest, paralysis and application of braces. Abaloparatide (ABL) is a synthetic peptide analog of PTHrP that has been shown to promote bone formation with limited bone resorption. ABL was approved by the FDA in 2017 to treat osteoporosis in postmenopausal women at high fracture risk. Yet, the ability of ABL to prevent bone loss in disuse is unknown. We hypothesized that ABL would prevent bone loss in the hindlimb unloading (HLU) rat model of disuse osteoporosis. Adult male Wistar rats, 13–14 weeks of age, were assigned to 1 of 4 groups (10 rats/group): ambulatory + vehicle (CON-VEH), ambulatory + ABL (CON-ABL), HLU + vehicle (HLU-VEH) or HLU + ABL (HLU-ABL). The rats received a daily subcutaneous injection of ABL (25µg/kg/day) or vehicle for 28 days. Blood serum was collected on day 0, 7, 14 and 28 to examine the expression of bone markers such as osteocalcin (OCN) and TRAcP5b. pQCT scans were acquired at the proximal tibia at day 0 and 28 to measure changes in the total and trabecular vBMD. Following euthanasia, trabecular (Tb) and cortical (Ct) bone microarchitecture from femurs, tibias and L4 vertebrae were assessed using µCT. Femurs were mechanically tested to failure in 3-point bending to determine ultimate load (N) and stiffness (N/mm). Treatment effects were evaluated using 2-way ANOVA. Effects were considered significant at p < 0.05. Data reported as mean±SD. HLU led to loss of bone density and structure that were prevented by ABL. Longitudinal pQCT revealed significant increases in total vBMD in ABL-CON (52±17%) vs. VEH-CON (20±5%); and in HLU-ABL (24±6%) vs. HLU-VEH (-2±3%) (p<0.001 for both). Significant differences were observed in the µCT analysis of the distal femur: Tb.BV/TV, thickness and BMD were 43.7%, 12.9% and 27.4% lower, respectively, in HLU-VEH compared to CON-VEH (p<0.05 for all). ABL prevented these negative effects, such that Tb.BV/TV, thickness and BMD were 66.5%, 39% and 50.3% higher in HLU-ABL compared to HLU-VEH (p<0.01 for all). A positive impact of ABL on bone morphology was also seen in the CON-VEH rats. CON-ABL had greater femoral stiffness (+22.9%, p=0.03) and ultimate load (+20.5%, p=0.01) than CON-VEH. Vertebral and tibial trabecular parameters mimicked the distal femur parameters. Serum TRAcP5b did not differ among groups, yet both ABL groups had higher OCN levels than the VEH-treated control groups (+63%, p<0.05). We demonstrated positive effects of ABL on BMD, trabecular bone mass and structure in both ambulating and unloaded rats. These results are consistent with prior studies showing positive effects of ABL on bone mass, structure and strength in OVX and ORX rats. Limits include only male rats and 1 dose of ABL. However, the results observed in this study provide a strong rationale for investigating the ability of ABL to prevent disuse bone loss in humans.